Correction: Ensemble-machine-learning-based correlation analysis of internal and band characteristics of thermoelectric materials. Issue 37 (18th September 2020) - Chen, Lihao; Xu, Ben; Chen, Jia; Bi, Ke; Li, Changjiao; Lu, Shengyu; Hu, Guosheng; Lin, Yuanhua
Abstract : Correction for 'Ensemble-machine-learning-based correlation analysis of internal and band characteristics of thermoelectric materials' by Lihao Chen et al., J. Mater. Chem. C, 2020, DOI: ; 10.1039/d0tc02855j .